2006
DOI: 10.1152/ajpheart.00024.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activation of brain renin-angiotensin-aldosterone system by central sodium in Wistar rats

Abstract: tional studies indicate that the sympathoexcitatory and pressor responses to an increase in cerebrospinal fluid (CSF) [Na ϩ ] by central infusion of Na ϩ -rich artificial cerebrospinal fluid (aCSF) in Wistar rats are mediated in the brain by mineralocorticoid receptor (MR) activation, ouabain-like compounds (OLC), and AT1-receptor stimulation. In the present study, we examined whether increasing CSF [Na ϩ ] by intracerebroventricular infusion of Na ϩ -rich aCSF activates MR and thereby increases OLC and compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 43 publications
1
65
0
2
Order By: Relevance
“…This pressor effect was partially blocked by the MR blocker eplerenone in SHRSPs, indicating that the effect of Na + might be mediated by MR activation. ICV infusion of the MR blockers, spironolactone 46 or benzamil, 47 prevented Na + -induced sympathoexcitatory and pressor responses in WKY rats. It has also been reported that ICV infusion of eplerenone attenuated ENaC expression in mice with pressure overload.…”
Section: Discussionmentioning
confidence: 91%
“…This pressor effect was partially blocked by the MR blocker eplerenone in SHRSPs, indicating that the effect of Na + might be mediated by MR activation. ICV infusion of the MR blockers, spironolactone 46 or benzamil, 47 prevented Na + -induced sympathoexcitatory and pressor responses in WKY rats. It has also been reported that ICV infusion of eplerenone attenuated ENaC expression in mice with pressure overload.…”
Section: Discussionmentioning
confidence: 91%
“…Plasma and brain aldosterone were measured by RIA as described previously (18). Briefly, plasma was applied to preconditioned C18 cartridges, the cartridges were washed with 12% methanol, and aldosterone was eluted with 80% methanol.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Intracerebroventricular infusion of Fab fragments that specifically bind ouabain-like compounds ("ouabain") (31) blocks these responses, whereas intracerebroventricular infusion of spironolactone or benzamil inhibits increases in brain "ouabain" and hypertension in response to chronic intracerebroventricular infusion of Na ϩ -rich aCSF (12,36,37). These findings suggest that mineralocorticoid receptors (MRs) and benzamil-blockable Na ϩ channels or transporters in the CNS mediate the release of "ouabain" and hypertension caused by a chronic increase in CSF [Na ϩ ].…”
mentioning
confidence: 99%